Improving Students’ English Vocabulary through Riddles Tehnique - Zein Mowuu; Moon Hidayati Otoluwa; Yunita Hatibie (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to investigate the effectiveness of using the Riddles Technique in enhancing the English vocabulary of seventh-grade students at SMP Negeri 15 Kota Gorontalo. The study focuses on determining whether this technique can significantly improve students’ vocabulary mastery. The research was conducted using a pre-experimental method with a one-group pre-test and post-test design. The population of this research consisted of all seventh-grade students, and the sample was class VII-1, comprising 20 students selected through purposive sampling. In the implementation phase, students were engaged in various vocabulary-based riddles during English lessons. These riddles were designed to stimulate students’ interest, challenge their thinking, and enhance their word retention. The pre-test was administered to assess the students’ initial vocabulary level, followed by a series of learning sessions using the Riddles Technique, and concluded with a post-test. The results indicated a significant improvement in students’ vocabulary scores. The mean score increased from 43 in the pre-test to 71 in the post-test. Furthermore, statistical analysis revealed that the significance value was 0.000, which is less than the standard alpha level of 0.05. This confirms that the alternative hypothesis (H₁) is accepted, indicating a significant effect of the Riddles Technique on vocabulary enhancement. In conclusion, the Riddles Technique proves to be an effective and engaging method for improving students’ English vocabulary. It is recommended for English language teachers as an innovative strategy to increase students’ participation and vocabulary acquisition.